Gastrointestinal Parasites With Their Risk Factors in Tharu Indigenous People in Southern Nepal: A Cross‐Sectional Study - Pinki Kumari Chaudhary; Tirth Raj Ghimire (Health Science Reports)
ABSTRACT Background Globally, gastrointestinal (GI) infections are common, particularly in populations with low socioeconomic levels, including high illiteracy rates, ignorance, poor housing and lifestyles, and unfavorable environmental conditions. These risk factors are the underlying cause of GI parasitic infections in many developing nations, including Nepal. Aim This study aimed to assess the prevalence and diversity of GI parasites and their association with a few risk factors within the marginalized indigenous Tharu people of the southern region of Nepal. Methods A purposive sampling method was used to collect stool samples from Tharu indigenous people (N = 179) in Thaskaul, Kolhabi, Bara, Nepal. The samples were preserved in a 2.5% potassium dichromate solution. The samples were analyzed by direct wet mount and acid‐fast staining techniques and examined at 40×, 100×, 400×, and 1000× magnifications. Results Out of 179 stool samples, the prevalence rate of the GI parasites was 42.46% (n = 76), out of which females (43.00%, 43/100) had a slightly higher prevalence rate than males (41.77%, 33/79) (p > 0.05, chi‐square tests at 95% confidence level). Out of nine species of GI parasites, the prevalence of Cryptosporidium spp. was highest among protozoa (30.17%, n = 54), whereas that of Ascaris lumbricoides was highest among helminths (5.59%, n = 10). Occupation, animal husbandry, parasitologic knowledge, drinking water sources, pork‐feeding habit, diarrheal or stomachache symptoms, and drug‐consuming history were associated with one or more GI parasitosis (p < 0.05). Conclusion The moderate prevalence and diversity of GI parasitism in the Tharu population suggests the need for effective, efficient, and timely preventative and control measures in the study area. Further One Health Approach, by conducting studies that involve the examination of samples from the local populations, livestock, food, water, and soil, would be important.